Exegese als Teil der Theologie - Vos, Christiane de (Forum Exegese und Hochschuldidaktik: Verstehen von Anfang an, 2022)
This article comments on the hiatus between university exegesis and church praxis from the perspective of church leadership. It sets in with subjective perceptions on the ambivalence that lies between the ideal of the importance of Biblical texts and the factual reality of their low significance in various areas of church life. Subsequently, four goals are presented, exegetical education at universities should aim at: a) the ability to perceive and express central messages of Biblical texts, b) and this against the background of their historical contexts; c) identifying and understanding innerbiblical and post-biblical reception processes; d) attaining a plurality of methodological approaches without losing the perspective for the whole of translating Biblical texts to today’s life. Important means to achieve this, are humility towards the texts, respecting the contexts of text production and reception, an awareness for one’s ordination on Bible and Confession, as well as modern re-conceptualizations of what norma normans and sola scriptura mean. The author pleads for a decided self-understanding of exegesis as part of theology as a whole, a stronger focus on higher education didactics in university teaching, reinforcing an explicitly theological stance in pastoral continued education, and a strengthened cooperation of church leaders and academic teachers.